Men’s image projection through discourse analysis - A. Alada, Joanne (Polaris Global Journal of Scholarly Research and Trends, 2023)
Speech acts are utterances that serve a function in communication. These speech acts were used to describe men’s images who are members of a fraternity. Fraternities exist due to the ideology of gender polarization. Power is central to men’s identities and this power is displayed through language use. This study investigated how language is used by the members of a fraternity to identify and assess men’s image and social status. It used a qualitative design using discourse analysis. This was done through transcribing and deconstructing a conversation or piece of text. The participants of the study were the members of a community-based fraternity group composed of college students, with ages ranging from 19-26 years old. Among the 40 members, there were at least eight members who were consistently present in three contexts of conversations: meetings, bonding sessions, and social gatherings, and were selected as participants of this study. The collection of data was done through recordings of men’s conversations with their consent. The data analysis procedure began with the recording of the conversations which were transcribed according to Kiesling’s (2008) transcription conventions. The researcher identified features in the text, such as themes in the text, especially those that relate to men’s images. A tape recorder was used to capture the actual words spoken by the participants and the transcription of data. This study suggested that behavior in the form of speech acts consistently manifested itself as an attribute of personality traits and the words men use to weave the images of who they are or are not.